1999
DOI: 10.1176/ps.50.10.1331
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians' and Clients' Perspectives on the Impact of Assertive Community Treatment

Abstract: These findings emphasize the importance of clients' perspectives in treatment planning and suggest that clinicians may overlook the smaller incremental steps toward improvement that are valued by clients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 47 publications
2
27
1
2
Order By: Relevance
“…In this study, social support was found to be the only significant factor associated with low hospitalization rate. Social support was found to be significantly associated with low rehospitalisation in an earlier study by Lang et al (1999). Other factors found in this earlier study to be significantly associated with hospitalization rate were factors related to symptoms as well as social, financial and legal factors; low levels of functioning and inadequate social support; dissatisfaction with family relations and socioeconomic status.…”
Section: Discussionsupporting
confidence: 42%
“…In this study, social support was found to be the only significant factor associated with low hospitalization rate. Social support was found to be significantly associated with low rehospitalisation in an earlier study by Lang et al (1999). Other factors found in this earlier study to be significantly associated with hospitalization rate were factors related to symptoms as well as social, financial and legal factors; low levels of functioning and inadequate social support; dissatisfaction with family relations and socioeconomic status.…”
Section: Discussionsupporting
confidence: 42%
“…Geralmente, são feitas análises e comparações entre as situações pré e pós-implementação dos programas em um mesmo serviço ou entre a situação no momento de entrada no serviço e a evolução depois de um período determinado pelo pesquisador (Borland et al, 1989;Curtis et al, 1996;Dixon et al, 1993a;Dixon et al,1993-b;Joannette et al, 2005;Lang et al, 1999;McGrew et al, 1995;Shaw et al, 1990;Tibbo et al, 1999;Wasylenki et al, 1993). Wasylenki et al (1993) mediram o impacto da participação no case management sobre uma população de desabrigados com doença mental comparando as situações anterior e posterior à entrada no programa.…”
Section: Resultsunclassified
“…Os estudos podem ter como objetivos descrever os programas e suas replicações ou adaptações, delinear o estado da pesquisa sobre o tema, apontar direções para futuras investigações, fazer comparações com outros serviços (Tabela 2) e análises de desfechos ou de eficácia, demonstrar benefícios para as populações-alvo e fazer comparações entre o PACT e o case management (Bandeira et al, 1998;Burns e Santos, 1995;Lang et al, 1999;Olfson, 1990;Phillips et al, 2001;Taube et al, 1990;Ziguras e Stuart, 2000). Taube et al (1990), em revisão bibliográfica sobre PACT, descrevem o programa, o comparam com abordagens tradicionais de cuidado comunitário -em especial programas dos centros comunitários de saúde mental (Tabela 2) -e sistematizam algumas direções para o futuro da pesquisa sobre o tema.…”
Section: Equipe Terapêuticaunclassified
“…Problems with narrative coherence have been observed in other samples with significant psychopathology, such as borderline personality disorder (Adler et al., ), as well as in samples with generally low psychological well‐being (e.g., Baerger & McAdams, ). Psychotherapy has often been construed as a process that is fundamentally concerned with enhancing the client's narrative coherence (e.g., Dimaggio, Salvatore, Azzara, & Catania, ; Neimeyer, Herrero, & Botella, ; Salvatore et al., ; Singer & Rexhaj, ). Cross‐sectional retrospective research has demonstrated that clients in good mental health recount their experiences in psychotherapy with a greater degree of narrative coherence than those who are worse off after treatment (Adler et al., ).…”
Section: Unitymentioning
confidence: 99%